The Effects of the Association Between a High-Fat Diet and Physical Exercise on BDNF Expression in the Hippocampus: A Comprehensive Review - Francisca Tayná da Silva Gomes; Antônio Vicente Dias de Andrade; Paloma Katlheen Moura Melo; Roque Ribeiro da Silva Júnior; Débora Lopes Silva de Souza; Élyssa Adriolly Freitas Tavares; Ingrid Garcia de Sena; Thales Allyrio Araújo de Medeiros Fernandes; Paulo Leonardo Araújo de Góis Morais; Ivana Alice Teixeira Fonseca; Cibele dos Santos Borges; José Rodolfo Lopes de Paiva Cavalcanti (Life, 2025)
High-fat diets, characterised by their high lipid content, have been associated with structural and functional alterations in the hippocampus of rodents, including a reduction in the expression of brain-derived neurotrophic factor (BDNF), which negatively impacts learning and memory. Evidence suggests that these impairments may be attenuated by regular physical exercise. This review aimed to gather relevant scientific evidence available on the effects of the association between high-fat diets and physical exercise on BDNF expression levels in the hippocampus of rats. The studies analysed highlight a neuroprotective effect of exercise, capable of positively modulating BDNF levels and, consequently, improving the cognitive functions of these animals.